2022
DOI: 10.1515/pac-2021-2009
|View full text |Cite
|
Sign up to set email alerts
|

IUPAC specification for the FAIR management of spectroscopic data in chemistry (IUPAC FAIRSpec) – guiding principles

Abstract: A set of guiding principles for the development of a standard for FAIR management of spectroscopic data are outlined and discussed. The principles form the basis for future recommendations of IUPAC Project 2019-031-1-024 specifying a detailed data model and metadata schema for describing the contents of an “IUPAC FAIRData Collection” and the organization of digital objects within that collection. Foremost among the recommendations will be a specification for an “IUPAC FAIRData Finding Aid” that describes the c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…It also makes it more difficult for reviewers to double-check the correctness of chemical names and structures in the data files, explaining the observed discrepancies between statements in the CML data and the text of the main publication. It is suggested that journals adopt publication rules mandating machine-readable mappings such as IUPAC FAIRSpec [ 42 ]. Such policy would make reviewing supplementary data easier and eliminate certain mistakes from the publication more readily.…”
Section: Resultsmentioning
confidence: 99%
“…It also makes it more difficult for reviewers to double-check the correctness of chemical names and structures in the data files, explaining the observed discrepancies between statements in the CML data and the text of the main publication. It is suggested that journals adopt publication rules mandating machine-readable mappings such as IUPAC FAIRSpec [ 42 ]. Such policy would make reviewing supplementary data easier and eliminate certain mistakes from the publication more readily.…”
Section: Resultsmentioning
confidence: 99%
“…For integration with DMPs, the RDA DMP common standard (Miksa et al 2020) can be applied, and on a more PaN specific level, the data model described in should be taken further. Other PaN relevant standards that need to be considered are: the the NeXus format standard for measurement files in PaN facilities (Könnecke et al 2015); related scientific techniques such as for spectroscopy described in Hanson et al (2022); and analytical chemistry in Rauh et al (2022).…”
Section: Next Stepsmentioning
confidence: 99%
“…Following some recent discoveries of fabricated crystallographic structures (Dauter & Baker, 2010;Else, 2022), the crystallographic community has increased its level of attention to data authenticity. In particular, calls have been made to include the original image data as a part of structure depositions (Hanson et al, 2022). In this regard, we observe that the generation of synthetic diffraction images as described in this report requires a major commitment of computational resources, which provides effective insurance against potential misuse of our methodology.…”
Section: Diffraction Photograph Simulationmentioning
confidence: 99%